Classificação multivariada de perfumes e análise de fragrâncias alérgenas - Gomes, Clerton Linhares (2015)
Perfumes are mainly made of ethilic alcohol, water and fragrances. These fragrances are responsible for caracterizarrem nice and unique odor of each perfume. The trade of this product perfumes is very lucrative for being product used by all. Parallel to the legal trade in perfumes, forgery see these products increasing in recent years. Among the fragrances, the highlight was a group of fragrances (limonene, benzyl alcohol, linalool, methyl octanoate, citral, citroneol, hidroxicitroleol, geraniol, eugenol, isoeugenol, anise alcohol, amyl cinnamic alcohol, amyl cinamal, cinnamic alcohol, coumarin, cinnamaldehyde, alpha-isometil ionene liral, lilial, farnesol hexilcinamaldeido benzyl benzoate, benzyl cinnamate, benzyl salicylate) that may cause allergy by contact, leading to dermatitis. Brazilian law (DRC 3/2012 ANVISA) and European (EC 1223/2009) state that when these concentrations exceed the limit of 0.01% (100 ppm) for products rinse and 0.001% (10 ppm) for products with rinse, the manufacturer is obliged to discriminate underin its label their presence. The first part of this work is the multivariate analysis of perfumes, based on the comparative study of 25 original perfumes ecom 25 false through oxidase analysis dose organic compounds by IR, GC-FID and espectroóscopia in the UV region (UV) : and inorganic by ion chromatography and flame photometry. The data generated were processed by a estatistic software, the R Project, giving the PCA, SIMCA and LDA, aiming to differentiate the original edo fake perfume. UV spectroscopy study showed that the original product had major quantity and intensity of bands compared to the fake product, which may be indicative of higher fragrance content. The chemometric treatment allowed the efficient separation into two groups. The analysis of ions and ethanol allowed to observe the fake product has high chloride content (38 ppm) and low ethanol (45%); since the original product had a low content of ions (15 ppm) and high ethanol content (83%). The multivariate study allowed the distinction of counterfeit and original products. The second part comes Dae analysis validation of allergenic fragrances in perfumes, extraídaso by solid phase microextraction and analyse by gas chromatography coupled to mass espectrometric the quadrupole type operating in SIM mode, with small sample size (10 μg.L -1). This method has shown good results of linearity, limit of detection (0,05 to 271 μg.L-1), limit of quantitation (0,017 to 0,900 μg.L-1), intermediate precision (3,0 to 19.3%) , repeatability (8,9 to 19,7%) and recovery (59-115%) for the studied matrix. The authentic perfumes analysis showed that these products have a high allergenic fragrance concentration (LD-190 mg.L-1) and need to be discriminated on their labels. The fake perfume analysis showed that these products have low allergenic fragrances have (LD-56 mg L-1) and who have no fragrances with higher molecular weight, as cinnamaldehyde and benzyl salicylate; this may be one of the reasons It makes the counterfeit product having a low fixing odor.